Analysis of the Electrostatic Precipitator (ESP) for Reducing Exhaust Gas Emissions from Nickel Smelter Processing in the Rotary Kiln Electric Furnace (RKEF) System - Rian Adrianto; Sinardi Sinardi (International Journal of Health Engineering and Technology, 2026)
This study aims to analyze the performance of the Electrostatic Precipitator (ESP) in reducing particulate concentration and exhaust gas emissions in the nickel processing process using the Rotary Kiln Electric Furnace (RKEF) system. The main variable observed was the variation of ESP electrode voltage at 20 kV, 30 kV, 40 kV, 50 kV, and 60 kV. The parameters measured included particulate concentrations before and after the ESP unit, as well as exhaust gas components consisting of sulfur dioxide (SO₂), nitrogen oxides (NOₓ), and carbon monoxide (CO). The results show that an increase in ESP voltage has a significant effect on improving particle collection efficiency. The highest efficiency was achieved at a voltage of 50 kV, reaching 94.94%, with particulate concentration decreasing from 158 mg/Nm³ to 8 mg/Nm³. However, at 60 kV the efficiency slightly decreased to 92.36% due to electrical field instability (spark discharge). In addition, exhaust gas concentrations also declined with increasing voltage, with the lowest values recorded at 50 kV: SO₂ at 405 mg/Nm³, NOₓ at 250 mg/Nm³, and CO at 100 mg/Nm³. Based on these findings, it can be concluded that the Electrostatic Precipitator (ESP) operates most optimally at a voltage of 50 kV, under operating conditions of approximately 135 °C gas temperature, 8–9% humidity, and dust resistivity ranging from 10¹⁰ to 10¹¹ Ω·cm. The ESP system has proven effective in reducing particulate emissions and maintaining exhaust gas concentrations below the emission quality standards stipulated in Regulation of the Minister of Environment and Forestry of Indonesia No. P.15/MENLHK/SETJEN/KUM.1/4/2019.